Textbook of microbiology for dental students - Ongole, Ravikiran; Arora, Brij Bala (New Delhi : CBS publishers & distributors, 2015)
Microbiology is an extremely diverse discipline and can be a bewildering field to the novice, particularly for dental students due to limited syllabus. Dental students are in a fix to take a particular book with limited time and syllabus. Such books are too long and detailed to be read by the typical dental student who is trying to keep up with several classes simultaneously of other dental subjects. The microbiology text presented here was written after 27 years of teaching medical and dental students and searching for a book that was both readable and complete enough to meet the needs of dental students. Textbook of Microbiology for Dental Students contains all of the information that is pertinent to the students who are studying microbiology keeping in mind their examination. This book also provides a solid background of microbiology while describing the organisms in a manner that is relevant to dental practice.
[A] general microbiology -- [CH 1] microbiology (A brief history) -- [CH 2] morphology and physiology of bacteria -- [CH 3] culture media and culture techniques -- [CH 4] selection, collection, transport and processing of clinical specimens, and identification of bacteria -- [CH 5] sterilization and disinfection -- [CH 6] chemotherapy -- [CH 7] bacterial genetics and drug resistance in bacteria -- [CH 8] infection -- [B] immunology -- [CH 9] immunity -- [CH 10] antigen and antibody -- [CH 11] the complement system -- [CH 12] antigen - antibody reactions -- [CH 13] structure and functions of immune system -- [CH 14] immune response -- [CH 15] hypersensitivity and autoimmunity -- [CH 16] immunodeficiency diseases -- [CH 17] immunology of transplantation and malignancy -- [CH 18] immunohaematology -- [C] Systemic bacteriology -- [CH 19] staphylococcus -- [CH 20]
Includes index.
Keywords: Mouth -- Microbiology; Medical microbiology